Cystatin C as a p53‐inducible apoptotic mediator that regulates cathepsin L activity. Issue 3 (4th March 2016) - Mori, Jinichi; Tanikawa, Chizu; Funauchi, Yuki; Lo, Paulisally Hau Yi; Nakamura, Yusuke; Matsuda, Koichi
Abstract : In response to various cellular stresses, p53 is activated and inhibits malignant transformation through the transcriptional regulation of its target genes. However, the full picture of the p53 downstream pathway still remains to be elucidated. Here we identified cystatin C, a major inhibitor of cathepsins, as a novel p53 target. In response to DNA damage, activated p53 induced cystatin C expression through p53 binding sequence in the first intron. We showed that cathepsin L activity was decreased in HCT116 p53 +/+ cells after adriamycin treatment, but not in HCT116 p53 −/− cells. We also found that knockdown of cystatin C reduced adriamycin‐induced caspase‐3 activation. Cystatin C expression was significantly downregulated in breast cancer cells with p53 mutations, and decreased cystatin C expression was associated with poor prognosis of breast cancer. Our findings revealed an important role of the p53–cystatin C pathway in human carcinogenesis. Abstract : Association of decreased cystatin C expression with p53 mutation.